2018
DOI: 10.1016/j.solmat.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of photothermal conversion using gold/water and MWCNT/water nanofluids

Abstract: This work experimentally investigated photothermal conversion behavior of Gold/water and MWCNT/water nanofluids at different volumetric concentrations (0.0001%-0.004% and 0.0001%-0.03%, respectively). The experiments were conducted for ~10 hours outdoor on each test day, without interruptions. The results show that the tested nanofluids have excellent photothermal conversion capability even under very low concentrations. Specific absorption rate (SAR) presented an exponential decay with increasing volumetric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 45 publications
0
27
0
2
Order By: Relevance
“…Nevertheless, the use of ethylene glycol alone in the heat transfer system is not a good choice because of its high viscosity, which is why most of the studies used its mixture with DI water. [19] Au one-step DI water 25-10 mg/L - [20] Au, CNT, Fe 3 O 4 two-step DI water 10-50 ppm - [21] Fe 3 O 4 two-step Water 1-5wt% - [22] Graphite two-step DI water/Paraffin -- [23] Au, MWCNT two-step DI water 0.0001-0.004vol% - [24] rGO, Ag-rGO two-step DI water 10-100 mg/L - [25] CuO two-step Paraffin 0.01-0.1wt% SSL [26] TiN, Au/TiN two-step EG 10-100 ppm - [27] CuO-MWCNT two-step DI water 0.01-0.25wt% - In the next section, the optical properties and photothermal energy conversion performance of various nanofluids are discussed and illustrated.…”
Section: Nanofluid Preparation For Solar Thermal Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the use of ethylene glycol alone in the heat transfer system is not a good choice because of its high viscosity, which is why most of the studies used its mixture with DI water. [19] Au one-step DI water 25-10 mg/L - [20] Au, CNT, Fe 3 O 4 two-step DI water 10-50 ppm - [21] Fe 3 O 4 two-step Water 1-5wt% - [22] Graphite two-step DI water/Paraffin -- [23] Au, MWCNT two-step DI water 0.0001-0.004vol% - [24] rGO, Ag-rGO two-step DI water 10-100 mg/L - [25] CuO two-step Paraffin 0.01-0.1wt% SSL [26] TiN, Au/TiN two-step EG 10-100 ppm - [27] CuO-MWCNT two-step DI water 0.01-0.25wt% - In the next section, the optical properties and photothermal energy conversion performance of various nanofluids are discussed and illustrated.…”
Section: Nanofluid Preparation For Solar Thermal Applicationsmentioning
confidence: 99%
“…To investigate the photothermal energy conversion performance of the working fluid, many researchers [23,28,37,42,48,56] utilized the photothermal energy conversion efficiency and specific absorption rate of the working fluid. For instance, the photothermal energy conversion efficiency can be calculated using Equation 4 [27]:…”
Section: Photothermal Energy Conversion Performance Of Nanofluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [5] studied the photothermal conversion property of Au nanofluids and found that efficiency increased with an increase in the volume fraction of nanoparticle. Experimental analysis on the photothermal conversion property of gold nanofluids was performed by Beicker et al [6]. Amjad et al [7] analyzed the photothermal conversion capability of different nanofluids to be used for direct absorption applications.…”
Section: Introductionmentioning
confidence: 99%
“…Beicker et al [23] investigated the photothermal conversion using different volume concentrations of gold/water and MWCNT/water nanofluids and found that both types of nanofluids showed perfect photothermal conversion even for very low concentrations. An increase in the range of 2-25% was observed by using 0.01 wt% graphite-based nanofluids.…”
Section: Introductionmentioning
confidence: 99%